2017
DOI: 10.1016/j.rbmo.2017.06.019
|View full text |Cite
|
Sign up to set email alerts
|

Weight decrease improves live birth rates in obese women undergoing IVF: a pilot study

Abstract: Obese women have lower pregnancy rates than normal-weight women undergoing assisted reproductive treatment. We conducted a pilot study to evaluate whether a 12-week diet and exercise intervention before an IVF cycle would influence pregnancy rates in obese women. Forty-one patients were enrolled in this study. They were randomly allocated to two groups: an intervention group (n = 21), who underwent an individualized diet and physical exercise programme supervised by a dietician, and a control group (n = 20), w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
38
0
6

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(44 citation statements)
references
References 29 publications
0
38
0
6
Order By: Relevance
“…Weight loss prior to either spontaneous conception or conception by IVF in obese women is recommended by international guidelines (15), but the data on optimal magnitude and timing are limited. Until now, short-term weight reduction directly before IVF has been assessed in a few prospective randomized controlled studies only (7,8,9,10,31). The results about reproductive outcomes of IVF are inconclusive.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Weight loss prior to either spontaneous conception or conception by IVF in obese women is recommended by international guidelines (15), but the data on optimal magnitude and timing are limited. Until now, short-term weight reduction directly before IVF has been assessed in a few prospective randomized controlled studies only (7,8,9,10,31). The results about reproductive outcomes of IVF are inconclusive.…”
Section: Discussionmentioning
confidence: 99%
“…Weight loss prior to IVF procedures has been associated with significantly improved pregnancy rates (PR) and live birth rates (7,8,9,10). Furthermore, a decreased number of IVF cycles required to achieve a pregnancy has also been reported after weight loss interventions (11).…”
Section: Introductionmentioning
confidence: 99%
“…According to our results, BMI did have an influence on clinical pregnancy rates and it was not affected by age. Espinos et al [11] suggested that weight loss results in a significantly increased cumulative live birth rate. However, not all studies find significant correlation between BMI and clinical pregnancy rate, recommending that BMI should not be a basis for IVF treatment denial [12].…”
Section: Discussionmentioning
confidence: 99%
“…There are a group of studies that suggest improved ovulatory frequency, pregnancy rates, and cost per pregnancy achieved in assisted reproduction [32,62]. One randomized controlled trial demonstrated that a 12-week diet and exercise program resulted in a mean weight loss of 5.4 kg in the intervention group, a trend toward a higher clinical pregnancy rate and a significant difference in live birth rates [63]. A secondary analysis of two parallel randomized controlled trials in obese PCOS women also demonstrated that deferred ovulation induction treatment preceded by lifestyle modification resulted in significantly improved ovulation rates and live birth rates when compared with immediate treatment [62].…”
Section: Lifestyle Intervention and Behavior Modificationmentioning
confidence: 99%